Cavitation Effect of Pure Water on Orifice Plate - HANGuihua; ZHAOEnyu; LIDawei; ZHAOZhiwei; CHENLinqiu; ZHUYipeng (Journal of Harbin University of Science and Technology, 2023)
In order to study the influence of structural parameters of orifice plate on cavitation effect , a gas-liquid two-phase dynamic cavitation model in orifice plate was established based on bubble dynamics theory , and the flow equations of orifice plate passage and outlet were derived. Under the initial operating parameters , the outlet pressure was fixed at 0 MPa , and the inlet pressure was adjusted. The pressure difference between the inlet pressure and outlet pressure was 0. 2 MPa ~ 1 MPa , and the equal difference value of 0. 1 MPa was incremented for nine times. The thickness of the orifice plate , the number of holes and the pore structure were changed. The effect of structural parameters of orifice plate on cavitation effect was studied. The results show that the cavitation strength of liquid becomes stronger with the increase of inlet pressure , and tends to be stable when the inlet pressure reaches a certain value. By changing the thickness of orifice plate , the conductivity of 8mm orifice plate reaches 140. 54 μS/cm when the pressure difference is between 0. 2 MPa and 0. 9 MPa , and the conductivity of 10 mm orifice plate reaches 142. 47 μS/cm when the pressure difference is between 0. 9 MPa and 1 MPa. Changing the number of holes in the orifice plate ,the conductivity of the five-hole plate is 136. 51 μS/cm when the pressure difference is between 0. 2 MPa ~ 0. 6 MPa , and the conductivity of the three-hole plate is 141. 61 μS/ cm when the pressure difference is between 0. 6 MPa ~ 1 MPa. Changing the pass structure , the pore structure and the pressure difference between 0. 2 MPa ~ 1 MPa , the influence of the pore shape on the cavitation strength of the orifice plate is weak , and the overall circular cavitation is the best , followed by the square one and the triangle one.